Students’ strategies in learning English autonomy: Narrative inquiry - Prasetya, Laksana Tri (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2023)
This study aims to investigate the students’ strategies in learning English autonomy. In this study, the students are majoring at non-English study program and they are graduated from the same standard senior high schools (not international school). However, based on the result of writer’s interview in English, there is only one or two of the students in one generation at STAI Darul Ulum Kandangan that their speaking competencies are regarded as higher than average students in their level. They could speak English very fluently with good pronunciation and could choose the correct dictions for their speaking. This study is qualitative research in the form of narrative inquiry. This study uses students’ life story as the source of data. In gaining the data, the writer uses semi-structured interview for the main source of data and questionnaire as the secondary data. The writer interviews two students of STAI Darul Ulum Kandangan who have those level of English. This study shows that the students have their own strategies in learning English autonomy outside of the classroom such as using pictures, social media, YouTube’s subtitles in learning English and so on. Therefore, the main strategies that they used are compensatory strategies. could be used by the teachers or lecturers to develop the students’ competencies in English especially in speaking and the teachers or lecturers could promote these strategies to the students who want to have good speaking English.